Diversidade genética e estruturação populacional em capivaras, Hydrochoerus hydrochaeris (Linnaeus, 1766) - Felix, Mariana Campanha (2022)
Decreased connectivity for species and consequently limited dispersal can be linked to various environmental factors such as climate, dispersal barriers, or limited dispersal. In the case of semi-aquatic organisms such as capybara, their dispersion can be influenced by the presence of water bodies. Our work aims to evaluate the distribution of genetic diversity of Hydrochoerus hydrochaeris in river basins of South America. We also evaluated the presence of structuring between different hydrographic basins and between hydrographic microbasins of the Paraguay and Alto Paraná basins in Brazilian territory. For this, we amplified a fragment of the D-loop region of mitochondrial DNA, constructed haplotype networks and performed phylogenetic and molecular analysis of variance. We also reconstructed a demographic history with the Bayesian Skyline Plot analysis. Our results showed that H. hydrochaeris populations are structured between the Orinoco, Paraguay and Alto Paraná basins, but still maintain ancestral polymorphisms and possibly a flow of individuals between the Paraguay and Alto Paraná basins. On the other hand, the genetic diversity, both haplotypic and nucleotide, in the Paraguay and Alto Paraná basins is high and the populations show a relatively recent demographic growth, the populations of the Orinoco basin show low diversity and a population decline. The patterns of structure and genetic diversity are probably a result of the distinct evolutionary history of watersheds and recent demographic fluctuations suffered by populations, respectively.